AKTIVITAS HARIAN DAN PERILAKU MAKAN BURUNG KAKATUA-KECIL JAMBUL KUNING (Cacatua Sulphurea Sulphurea Gmelin, 1788) DI PENANGKARAN - Anindya Gitta; Burhanuddin Masy'ud; Erna Suzanna (Department of Forest Resources Conservation and Ecotourism - IPB University, 2012)
A total of 12 activities were observed from the cockatoo in captivity i.e walking activity, pecking at object, motionless, moving slightly, reserving, exploring fur, eating, calling, drinking, defecating, and other activities. Differences activities between male and female cockatoo where classified into other activities. Other activities carried out by male cockatoo were playing activity, checking condition, flapping its wing, hanging and spinning, and hiding. Other activities carried out by female cockatoo were spreading its right wing and the cleaning its feet. The most frequent activity performed by the male cockatoo was playing activity, while most frequent activity carried out by a female cockatoo was a motionless activity.Male showed more active than female. In terms of feeding behavior, there was no difference between male and female cockatoo. Cockatoos use one leg for gripping a branch or perched on a place, and the other leg for holding itsfeed. Another way of feeding activity was to eat the feed directly. Keywords:Cockatoo, captivity, daily activites, feeding behavior